Development of Modular Arduino-Based Learning Kit for AC Motor Speed Control - MOHD LATIF, MUHAMMAD SYAFIQ ITQAN; NORJALI, RASIDA; MD JAMAL, NOREZMI (Progress in Engineering Application and Technology, 2025)
This project presents an Arduino-based learning kit capable of teaching AC motor speed control,and real-time monitoring.This kit includes the Arduino microcontroller,motor drivers and sensors that measure speed,voltage,current and temperature.The users are able to use tools such as PWM and closed-loop feedback and continue to build upon their theoretical and practical knowledge.The learning kit includes a MATLAB to visualize the performance in real-time and the option to customize learning materials,allowing for unique curriculum designs.The modular nature of the learning kit is consistent with various learning curves.The learning kit suitable for learners at any point in education or training.The goal is to lessen the gap between the theory and practical sides of getting people invoved in control motor speed.